The Practice of Heritage Building Conservation in Kuala Lumpur, Malaysia - Noorizam, Nukhairiah Sakinah (2014)
Conservation of heritage buildings was first initiated in Malaysia in 1970's. The efforts of conserving these buildings may bring massive amount of benefits to the country and into the construction industry. Government and different kinds of ministeries are said to be responsible of such practice, However, the awareness among the all level of society is also important. Professionals from the construction industry play an important role in making this efforts successful. However, are these professional aware on the practice and the benefits to withstand these buildings at present? Whether or not it is important to them? What about their current status of such practice? This research aims to study current situation of development practice in heritage building conservation besides, reviewing the level of awareness of heritage building conversation in Malaysia construction industry, particularly in Kuala Lumpur.